2006
DOI: 10.1021/la061943y
|View full text |Cite
|
Sign up to set email alerts
|

Density Depletion at Solid−Liquid Interfaces:  a Neutron Reflectivity Study

Abstract: Neutron reflectivity experiments conducted on self-assembled monolayers (SAMs) against polar (water) and nonpolar (organic) liquid phases reveal further evidence for a density reduction at hydrophobic-hydrophilic interfaces. The density depletion is found at the interface between hydrophobic dodecanethiol (C12) and hexadecanethiol (C16) SAMs and water and also between hydrophilic SAMs (C12/C11OH) and nonpolar fluids. The results show that the density deficit of a fluid in the boundary layer is not unique to aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
110
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 48 publications
16
110
1
Order By: Relevance
“…As a result, we obtained a surface which was completely wetted by hexadecane, corresponding to an interfacial energy of γ sl = 34 mJ/m 2 at room temperature. 6,13 For the lower interfacial energy substrate another identically cleaned silicon wafer was subsequently chemically coated with an OTS monolayer by immersing it in a solution of 50 g bicyclohexane, 2.8 g carbon tetrachloride, and 0.8 g OTS for 15 min and flushing afterward with chloroform to remove any cross-linked OTS chains. This procedure was repeated three times to ensure a fully covered substrate, and the resulting advancing contact angle of hexadecane was 40 • ± 2 • at 22 • C, 39 • ± 2 • at 40 • C, and 37.3 • ± 2 • at 60 • C. This corresponds to an interfacial energy of γ sl = 7.2 mJ/m 2 at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, we obtained a surface which was completely wetted by hexadecane, corresponding to an interfacial energy of γ sl = 34 mJ/m 2 at room temperature. 6,13 For the lower interfacial energy substrate another identically cleaned silicon wafer was subsequently chemically coated with an OTS monolayer by immersing it in a solution of 50 g bicyclohexane, 2.8 g carbon tetrachloride, and 0.8 g OTS for 15 min and flushing afterward with chloroform to remove any cross-linked OTS chains. This procedure was repeated three times to ensure a fully covered substrate, and the resulting advancing contact angle of hexadecane was 40 • ± 2 • at 22 • C, 39 • ± 2 • at 40 • C, and 37.3 • ± 2 • at 60 • C. This corresponds to an interfacial energy of γ sl = 7.2 mJ/m 2 at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…6 Note that in the present study the depletion layer can be modeled separately from the SAM due to the high resolution of the instrument, and, therefore, no reference system is needed anymore, which could introduce a systematic error. A further indication of the intrinsic nature of the observed depletion at the OTS/d-hexadecane interface is the enhancement of the depletion distance with temperature.…”
Section: A Low Interfacial Energy Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…In reality, although the water-hydrophobic interface has been studied by a number of groups, [30][31][32][33][34][35][36][37] the results are inconsistent and have not led to a consensus. Early neutron reflectivity studies [31][32][33] of hydrocarbon-water interfaces reported gap widths larger than 10Å, while later x-ray reflectivity measurements on similar systems reported gap widths of less than 5Å.…”
Section: Introductionmentioning
confidence: 99%
“…Thus silicon-supported SAMs provide excellent, well-defined hydrophobic surfaces that have been used in many experimental studies. [31][32][33][35][36][37] However, there is a high price: the system now contains at least three interfaces, namely silicon-oxide, oxide-SAM, and SAM-water. Only the last of these is of interest here, but all interfaces reflect X-rays or neutrons and must be accounted for during data analysis.…”
Section: Introductionmentioning
confidence: 99%